Chromatin-remodeling and the initiation of transcription. Issue 4 (16th July 2015) - Lorch, Yahli; Kornberg, Roger D.
Abstract: The nucleosome serves as a general gene repressor by the occlusion of regulatory and promoter DNA sequences. Repression is relieved by the SWI/SNF-RSC family of chromatin-remodeling complexes. Research reviewed here has revealed the essential features of the remodeling process.